Impacts of transportation sector emissions on future U.S. air quality in a changing climate. Part I: Projected emissions, simulation design, and model evaluation. (July 2018) - Campbell, Patrick; Zhang, Yang; Yan, Fang; Lu, Zifeng; Streets, David
Abstract: Emissions from the transportation sector are rapidly changing worldwide; however, the interplay of such emission changes in the face of climate change are not as well understood. This two-part study examines the impact of projected emissions from the U.S. transportation sector (Part I) on ambient air quality in the face of climate change (Part II). In Part I of this study, we describe the methodology and results of a novel Technology Driver Model (see graphical abstract) that includes 1) transportation emission projections (including on-road vehicles, non-road engines, aircraft, rail, and ship) derived from a dynamic technology model that accounts for various technology and policy options under an IPCC emission scenario, and 2) the configuration/evaluation of a dynamically downscaled Weather Research and Forecasting/Community Multiscale Air Quality modeling system. By 2046–2050, the annual domain-average transportation emissions of carbon monoxide (CO), nitrogen oxides (NOx ), volatile organic compounds (VOCs), ammonia (NH3 ), and sulfur dioxide (SO2 ) are projected to decrease over the continental U.S. The decreases in gaseous emissions are mainly due to reduced emissions from on-road vehicles and non-road engines, which exhibit spatial and seasonal variations across the U.S. Although particulate matter (PM) emissions widely decrease, some areas in the U.S. experience relatively large increases due to increases in ship emissions. The on-road vehicle emissions dominate the emission changes for CO, NOx, VOC, and NH3, while emissions from both the on-road and non-road modes have strong contributions to PM and SO2 emission changes. The evaluation of the baseline 2005 WRF simulation indicates that annual biases are close to or within the acceptable criteria for meteorological performance in the literature, and there is an overall good agreement in the 2005 CMAQ simulations of chemical variables against both surface and satellite observations. Graphical abstract: Image 1 Highlights: Detailed technology-driven transportation emissions are presented for the U.S. Transportation emissions are projected to decrease by 2046–2050 for the U.S. On-road vehicles dominate emission changes of CO, NOx, VOC, and NH3 . On-road and non-road modes both contribute to SO2 and particulate emission changes. Overall good model performance for baseline 2005 WRF/CMAQ simulation. Abstract : The methodology of a novel Technology Driver Model are presented and evaluated, and the technology-driven transportation emission projections show overall decreases for the U.S.